ChemInform Abstract: Broensted Acid‐Catalyzed Phenylselenenylation of Internal Olefins. Issue 34 (August 2015) - Wu, Ping; Huang, Fei; Lou, Jiang; Wang, Quannan; Liu, Zhuqing; Yu, Zhengkun
Abstract Treatment of olefins (I) and (VI) with phenylseleno reagent (II) affords selenated products.